2009
DOI: 10.1590/s0103-84782009005000254
|View full text |Cite
|
Sign up to set email alerts
|

Eficácia de resíduos da bananicultura sobre a inibição do desenvolvimento larval em Haemonchus spp. provenientes de ovinos

Abstract: Com o presente estudo, foi avaliada a eficácia in vitro de extratos vegetais de resíduos da bananicultura sobre a inibição do desenvolvimento larval de nematódeos gastrintestinais de ovinos. A técnica de coprocultura quantitativa e qualitativa foi empregada para avaliar a eficácia anti-helmíntica dos extratos aquosos de folhas, pseudocaules e corações de bananeiras da cultivar 'Prata Anã', nas concentrações 25, 75 e 150mg mL-1, em um delineamento inteiramente casualizado. Os resultados obtidos demonstraram que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 3 publications
(3 reference statements)
1
7
0
8
Order By: Relevance
“…both in vitro and in vivo. The aqueous extraction method used by Oliveira et al (2010) reinforces this hypothesis because it required heating the samples at 60 ºC for one hour, which would denature most condensed tannins. Although we did not observe a decrease in FECs in either trial, a significant reduction in in vitro EHT was observed in the animals infected with T. colubriformis, demonstrating an inhibitory effect of the banana leaf on egg development.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…both in vitro and in vivo. The aqueous extraction method used by Oliveira et al (2010) reinforces this hypothesis because it required heating the samples at 60 ºC for one hour, which would denature most condensed tannins. Although we did not observe a decrease in FECs in either trial, a significant reduction in in vitro EHT was observed in the animals infected with T. colubriformis, demonstrating an inhibitory effect of the banana leaf on egg development.…”
Section: Discussionmentioning
confidence: 93%
“…The anthelmintic effect of the banana plant has been studied both in vitro and in vivo. Aqueous extracts from the leaves, false stems and flowering stalks of banana plants significantly reduced the in vitro recovery of Haemonchus larvae from pooled faeces from naturally infected sheep, with the average reduction in worm recovery ranging from 98.5 to 100% (Oliveira et al, 2010). Lambs that were artificially infected with H. contortus and fed with banana plant leaves for 21 consecutive days demonstrated significant FECs reduction compared with the control group, suggesting that the treatment reduced the fecundity of the worms (Marie-Magdalene et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Em estudo conduzido por Macedo et al (2009), utilizando óleo essencial de Eucalyptus globulus na concentração de 43,5mg/mL, foi demonstrado 98,7% de inibição do desenvolvimento larval. Extrato aquoso de Musa sp., avaliado na concentração de 57,76mg/mL apresentou eficácia de 90% (Oliveira et al, 2010). Extratos de folhas e sementes produzidos com acetona, etilacetato e metanol produzidos com Annona squamosa, Eclipta prostrata, Solanum torvum, Terminalia chebula e Catharanthus roseus mostraram completa inibição (100%) quando utilizados na concentração de 50mg/mL (Kamaraj e Rahuman, 2011).…”
Section: Resultsunclassified
“…A atividade anti-helmíntica dos taninos condensados, presentes nas plantas taniníferas, já foi avaliada in vitro, por diversos autores (ALEMÁN et al, 2011;GOMES et al, 2010;OLIVEIRA et al, 2010) por ter como vantagens baixo custo, rapidez dos resultados, permitir a triagem de uma grande quantidade de plantas e possibilidade de avaliar substâncias isoladas sem interferência de outros compostos (GITHIORI; ATHANASIADOU; . Min e Hart (2003) apresentaram resultados demonstrando o efeito dos taninos condensados, frente a uma resposta imune ao parasitismo em animais, quando comparados com um controle de forragem com baixo teor do mesmo.…”
Section: Fonte: Elaboração Dos Autoresunclassified
“…A eficácia dessas plantas são, geralmente, sobre redução no número médio de ovos por grama de fezes (OPG) que foram observadas por Almeida et al (2007), Max et al (2009), Minho et al (2008a, Parra et al (2011) e Silva et al (2010.…”
Section: Introductionunclassified